TEORI AKUNTANSI MASA KINI - Paranoan, Selmita (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
This paper presents the development of the scope of accounting theory because of the growing need for information which is presented in the financial statements. The specific objective of financial statements is to present the consolidated financial position, results of operations, and changes in financial position in accordance GAAP (General Accepted Accounting Principles). The definition of this accounting purposes have weaknesses or limitations.Critics of the limitations of conventional accounting that must be done parallelization with practices in the present economic institutions that continue to grow with various forms of economic transaction of business done. This paper discusses the five major developments in accounting theory scope of the present and future who attempt to address the above challenges, namely: Accounting for the public economy (accounting socioeconomic); Accounting for human resources (human resources accounting); Accounting for the cost of capital (accounting for the cost of capital); Report of financial forecasts (reporting of Financial forecasts); The trend towards multi-national accounting. This proves, that the accounting as a science must continue to conduct research and intensive studies to give birth to the theory of accounting in accordance with the needs of economic civilization of the present and future need.